Is securitization theory racist? Civilizationism, methodological whiteness, and antiblack thought in the Copenhagen School. (February 2020) - Howell, Alison; Richter-Montpetit, Melanie
This article provides the first excavation of the foundational role of racist thought in securitization theory. We demonstrate that Copenhagen School securitization theory is structured not only by Eurocentrism but also by civilizationism, methodological whiteness, and antiblack racism. Classic securitization theory advances a conceptualization of 'normal politics' as reasoned, civilized dialogue, and securitization as a potential regression into a racially coded uncivilized 'state of nature'. It justifies this through a civilizationist history of the world that privileges Europe as the apex of civilized 'desecuritization', sanitizing its violent (settler-) colonial projects and the racial violence of normal liberal politics. It then constructs a methodologically and normatively white framework that uses speech act theory to locate 'progress' towards normal politics and desecuritization in Europe, making becoming like Europe a moral imperative. Using ostensibly neutral terms, securitization theory prioritizes order over justice, positioning the securitization theorist as the defender of (white) 'civilized politics' against (racialized) 'primal anarchy'. Antiblackness is a crucial building-block in this conceptual edifice: securitization theory finds 'primal anarchy' especially in 'Africa', casting it as an irrationally oversecuritized foil to 'civilized politics'. We conclude by discussing whether the theory, or even just the concept of securitization, can be recuperated from these racist foundations.